NURSING CONDUCT IN THE TREATMENT OF VULVOVAGINITIS IN THE GESTATIONAL PERIOD - Adélia de Paula Sousa, Emmir; Caroline de Souza, Anne; de Lira Silva, Macerlane; Ruston de Oliveira Braga, Thárcio (Health and Society, 2022)
Introduction: One of the most frequent complaints of women during the gestational period is vulvovaginitis, which are infections that affect the female genitalia. When you have contact with an infectious agent, such as microorganisms, parasites, bacteria, viruses or fungi. Therefore, it is of fundamental importance that the nursing professional has knowledge about these infections, and that treatment strategies are carried out according to the clinical needs of the patient. Objective: To identify the main guidelines on treatment for vulvovaginitis during pregnancy. Methodology: The present study is an integrative literature review, carried out through a bibliographic survey in scientific databases of electronic libraries: Latin American and Caribbean Literature on Health Sciences (LILACS), Bases Data on Nursing (BDENF) and Scientific Electronic Library Online (SCIELO), where the eligibility criteria defined for sample selection and composing research results were applied. Results and Discussions: From the analysis of the literature, it was shown that most cases of vulvovaginitis are associated with multiple or new sexual partners, as well as the non-use of condoms and even vaginal douches. Vaginal douches can cause an imbalance in the PH and consequently in the vaginal bacterial flora, leaving the region more susceptible to infections. In this process of vaginal infections during pregnancy, the nursing professional plays an essential role in the diagnosis and treatment of these pregnant women. During prenatal consultations, the nurse may be questioning the pregnant woman about symptoms and signs suggestive of sexual infection, because the earlier the diagnosis, the better the treatment response. Conclusion: Health education is the main method of guidance for pregnant women. Always in prenatal consultations, the same should be oriented as to risk factors and prevention methods, always oriented to adherence to eating habits, hygiene of the intimate region and practice of physical activities, because the best way of treating vulvovaginitis is prevention.